2020
DOI: 10.3892/or.2020.7478
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of SLCO4C1 inhibits cell proliferation and metastasis in endometrial cancer through inactivating the PI3K/Akt signaling pathway

Abstract: Endometrial cancer (EC) is the second leading type of cancer among women, and its progression is dependent on several factors. The aim of the present study was to examine the effect of solute carrier organic anion transporter family member 4C1 (SLCO4C1) on human EC and determine the underlying molecular mechanism. A total of 57 differentially expressed genes associated with advanced stage and survival were identified in The Cancer Genome Atlas database. In addition, gene ontology analysis indicated that SLCO4C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 25 publications
(32 reference statements)
0
18
0
Order By: Relevance
“…[30][31][32] Meanwhile, the PI3K/AKT signaling pathway takes part in tumor metastasis. 33 Intriguingly, it has been reported that PI3K/ AKT signaling pathway can be regulated by lncRNAs. 34,35 TM4SF1-AS1 is located on chromosome 3q25.1 region and is the antisense RNA of TM4SF1.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32] Meanwhile, the PI3K/AKT signaling pathway takes part in tumor metastasis. 33 Intriguingly, it has been reported that PI3K/ AKT signaling pathway can be regulated by lncRNAs. 34,35 TM4SF1-AS1 is located on chromosome 3q25.1 region and is the antisense RNA of TM4SF1.…”
Section: Discussionmentioning
confidence: 99%
“…There are very limited data available about expression of SLC51B and SLC51A in cancer [ 45 ]. Interestingly, OATP1B3 and OATP4C1 are the only E1-S transporters that have previously been investigated in EC tissue [ 28 , 47 ]. The levels of OATP4C1 were found to be higher in EC compared to normal endometrial tissue where the expression of SLCO4C1 correlates positively with disease progression [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, OATP1B3 and OATP4C1 are the only E1-S transporters that have previously been investigated in EC tissue [ 28 , 47 ]. The levels of OATP4C1 were found to be higher in EC compared to normal endometrial tissue where the expression of SLCO4C1 correlates positively with disease progression [ 47 ]. We observed no difference in SLCO4C1 expression in EC versus adjacent control tissues and found no association with any of the prognostic factors probably due to the fact that our cohort included mostly low-grade EC samples (26 low grade and 10 high grade).…”
Section: Discussionmentioning
confidence: 99%
“…Altered OATP4C1 expression has been linked to CVD events [ 146 , 243 ] ( Table 4 ) and endometrial cancer tissues [ 209 ], and genetic variants of the SLCO4C1 gene were also found to be associated with obesity [ 244 ]. Increased expression of human OATP4C1 in a transgenic rat kidney model leads to an increased excretion of uremic toxins and reduced hypertension and cardiomegaly [ 146 , 243 ].…”
Section: Transporter Families Shown To Transport L-arginine And/ormentioning
confidence: 99%